Ethical hacking : learning the basics - Gupta, Sunil (Apress, 2018)
"The video is divided into six sections, covering various aspects of ethical hacking for a beginner to grasp. Starting with an introduction to the basics of ethical hacking, you will go through common terminologies used and also learn to install your first virtual machine. You will then take a look at various Linux terminal commands and also learn to perform basic operations with them. The following sections will introduce footprinting and vulnerability scanning, where you will learn how these processes work by going through examples. In conclusion, you will learn what exploitation is and how a minor vulnerability in the system can lead to a breach."--Resource description page